Toilet Training Program Using the Brazelton Child-Oriented Method for Early Childhood - Eliza, Eliza; Priyanti, Nita (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study examines implementing a toilet training program using the child-oriented Brazelton method at TKIT Ar-Rahman 1. Employing a qualitative descriptive approach, five children aged 5-6 years participated as research subjects. Data were gathered through non-participant observation and documentation and analyzed using the Miles and Huberman model. The findings underscore the effectiveness of the Brazelton method in enhancing children's independence in toilet use by focusing on readiness and gradual development. This approach prioritizes children's comfort and emotional safety, enabling tailored interventions that respect their developmental trajectories. Teachers played a pivotal role by offering consistent guidance supported by visual and verbal aids, while parental involvement strengthened the outcomes. The holistic nature of the Brazelton method, including its emphasis on collaboration and physiological readiness, addresses individual challenges effectively. This study provides practical recommendations for adopting the Brazelton method across diverse educational settings, promoting a balance between developmental support and structured training. The results improve child independence, foster self-regulation, and create a more efficient learning environment.